Pengaruh Ketersediaan Fasilitas Kerja Terhadap Kinerja Pegawai di Kantor Brigade Siaga Bencana Kabupaten Bantaeng - Mansur, Dwi Regina Markanita; Setiawati, Budi; Parawu, Hafiz Elfiansyah (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2020)
This study aimed to determine how big the influence of work facilities to the employee performance at  Bantaeng Regency Disaster Preparedness Brigade Office. This study  used quantitative methods with the type of survey research and data collection techniques were observation and questionnaires. The population in this study were all employees in the Bantaeng Regency Disaster Preparedness Brigade Office, with a total sample of 50 people. In addition, sampling used a saturated sampling technique. The results of this study showed that the work facilities consisted of in accordance with the needs, were able to optimize work results, were easy to use, accelerated the work process, the placement was arranged properly having a contribution of 34.2% to the performance of employees in the Bantaeng District Disaster Preparedness Brigade Office, while 65.8% was influenced by other factors not examined in this study.